Micro-Credentialing: The Janus of Higher Education - Schutte, Flip (International Review of Management and Marketing, 2024)
The use of micro-credentials holds immense potential to address the challenges of traditional higher education, particularly in terms of accessibility, employability, and inclusivity. This study delves into the rise of micro-credentialing and its evolution in the digital learning landscape post the COVID-19 pandemic. With many people owning cell phones and a tech-savvy younger generation, micro-credentials are poised to pave a promising pathway for education and career advancement. The research explores the potential, benefits, and possible future of micro-credentials. Using an integrative literature review approach, this study uses a qualitative approach to analyse policy documents, published articles, and case studies of micro-credentialing initiatives. According to initial research, micro-credentials have the potential to provide adaptable and targeted learning opportunities. These can be combined and aligned with industry standards, bridging the divide between traditional education and the evolving requirements of the job market. This adaptability instils confidence in the relevance of the education system. Micro-credentialing is a new way of recognising and certifying skills. It is more inclusive and challenges traditional education models, offering a lifelong learning and employability framework.